MASTERING TEACHING ENGLISH FOR YOUNG LEARNERS - Lobar Hamro qizi, Muratbayeva; Sulayman Javlanbek o`g`li , Abdisheribov (Scientific Impulse, 2023)
Teaching language to old learners differs from teaching language to young learners. Young learners have certain characteristics that are different from old learners that influence their foreign language acquisition. Teaching a foreign language is easy if we understand the rules well. The rules are to understand the characteristics of our students, to master some suitable methods and to choose suitable material. Young learners have certain characteristics that set them apart from older learners. In relation to certain characteristics, the teacher must understand to differentiate the method he uses to teach the young learners English as a foreign language. In order to strengthen the teaching, the teacher must have a good command of the material.